High-transmittance super-weather-resistant protective film as well as preparation method and application thereof
The existing self-adhesive films are solved in weather resistance and light transmittance by using styrene-based thermoplastic elastomers, tackifying resins and maleic anhydride grafted polypropylene in the self-adhesive layer composition, combining specific light absorbers and light stabilizers. In addition, high-transmittance and superweather-resistant protective film with high light transmittance and weather resistance is achieved, which is suitable for protection of exposed environments such as elevators.
Patent Information
- Application Number
- CN202411540835.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-31
AI Technical Summary
The existing self-adhesive films have shortcomings in improving weather resistance and light transmittance, especially in ultraviolet rays and high temperature and high humidity environments, and waste manpower and material resources during the preparation process.
Using a self-adhesive layer composition, including styrene-based thermoplastic elastomer, tackifying resin and maleic anhydride grafted polypropylene, a specific ratio of light absorber and light stabilizer, it has excellent light transmittance and weather resistance. High-transparency ultraweather-resistant protective film.
It achieves high light transmittance and good weather resistance, has appropriate peeling force, significantly improved UV resistance and high temperature and humidity performance, avoiding white spots on the surface of the material, and has high industrial production efficiency.
Smart Images

Figure BDA0005112753110000081 
Figure BDA0005112753110000091 
Figure BDA0005112753110000092
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a high-transmittance and ultra-weather-resistant protective film and a preparation method and application thereof. Background Art
[0002] In recent years, with the development of economy and society, people have put forward new demands on the quality of life while pursuing high-quality products. Therefore, the number of existing elevators has gradually increased. In addition, due to the existence of external forces such as friction during the transportation and use of elevators, it is necessary to consider protecting the surface of materials for the sake of beauty and prevent dust and corrosive gases from damaging the surface of objects. In particular, many elevators are directly exposed to the outdoor environment, so the protection of elevators is particularly important. Self-adhesive film is a kind of protective film that does not require glue coating. It can adhere to the surface of the object through the self-adhesive layer of the film. The protective film is removed during assembly or use to protect the surface of the material.
[0003] The self-adhesive film provided in the prior art is a multi-layer co-extrusion film with white masterbatch and black masterbatch added to the middle layer and the surface layer to play a covering role, thereby protecting the adhesive layer, but this also affects the appearance later, and wastes manpower and material resources in the preparation process. Patent CN 109367146 A discloses a super weather-resistant solar cell protective film and a preparation method thereof, which uses PVDF as a barrier layer, adds a portion of the barrier layer, adds a portion of the ultraviolet absorber and a mineral filler as a light absorber to prepare a weather-resistant film, but the addition of the mineral ultraviolet absorber causes the light transmittance of the material to decrease and affects the light transmittance of the material. Summary of the invention
[0004] Based on the defects of the prior art, the purpose of the present invention is to provide a high-transmittance and super-weather-resistant protective film with excellent light transmittance, good weather resistance and suitable self-adhesion, and a preparation method and application thereof.
[0005] In order to achieve the above object, in a first aspect of the present invention, the present invention provides a self-adhesive layer composition, the self-adhesive layer composition comprising the following components in parts by weight: 53-82 parts of styrene-based thermoplastic elastomers (SBCs), 13-37 parts of tackifying resin, 2-9 parts of maleic anhydride grafted polypropylene, and 0.1-1 parts of weathering additives;
[0006] The weathering agent comprises a light absorber and a light stabilizer, wherein the mass ratio of the light absorber to the light stabilizer is light absorber:light stabilizer=(1-1.5):1;
[0007] The light absorber includes at least one of 2-hydroxy-4-n-octyloxybenzophenone and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol;
[0008] The light stabilizer includes at least one of a polymeric hindered amine light stabilizer and 1,5,8,12-tetrakis[4,6-bis(N-butyl-N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane, and the average molecular weight of the light stabilizer is 2000-3000.
[0009] The present invention provides a self-adhesive layer composition. By optimizing the components and the formula of the self-adhesive layer and limiting the parameters of the components, the obtained self-adhesive layer composition can be applied to the preparation of a subsequent protective film. The composition has suitable peeling force and excellent light transmittance and weather resistance. Specifically, the composition has excellent resistance to ultraviolet rays and resistance to high temperature and humidity.
[0010] Specifically, a specific type of light absorber and a specific type and a specific average molecular weight range of light stabilizer can achieve an excellent compounding effect under the synergistic effect of maleic anhydride grafted polypropylene, thereby obtaining good UV resistance and high temperature and humidity resistance of the product, while preventing the problem of white spots on the surface of the material due to precipitation; and can also ensure that the product has excellent light transmittance.
[0011] The average molecular weight of the light stabilizer was characterized by using gel permeation chromatography (GPC).
[0012] Exemplarily, the styrene elastomer may be any point value or any two point range value between 53-82 parts, such as 55-80 parts, or 53 parts, 55 parts, 58 parts, 60 parts, 62 parts, 64 parts, 66 parts, 68 parts, 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, 80 parts, 82 parts, etc.; the tackifying resin may be any point value or any two point range value between 13-37 parts, such as 15-35 parts, or 13 parts, 15 parts, 18 parts, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts , 30 parts, 32 parts, 34 parts, 36 parts, 37 parts, etc.; the maleic anhydride grafted polypropylene can be any point value or any two point range value between 2-9 parts, for example, it can be 3-8 parts, or it can be 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, etc.; the weathering additive can be any point value or any two point range value between 0.1-1 parts, for example, it can be 0.2-0.9 parts, or it can be 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, 1.0 parts, etc.
[0013] Exemplarily, the mass ratio of the light absorber to the light stabilizer may be any point value or any range value between (1-1.5):1, such as 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, etc.
[0014] Exemplarily, the average molecular weight of the light stabilizer may be any point value or any two point range values between 2000-3000, for example, 2000, 2100, 2200, 2300, 2400, 2500, 2600, 2700, 2800, 2900, 3000, etc.
[0015] Preferably, in the self-adhesive layer composition, the mass percentage of the weathering aid is 0.07-1.5%, and the mass percentage of the maleic anhydride grafted polypropylene is 1.5-12%.
[0016] As a preferred embodiment of the self-adhesive layer composition of the present invention, the self-adhesive layer composition comprises the following components in parts by weight: 5-6 parts of maleic anhydride grafted polypropylene and 0.4-0.6 parts of a weathering aid.
[0017] The present invention has found that maleic anhydride grafted polypropylene can have a good compounding effect with a weathering additive, and especially when the mass parts of the two are further selected to be within the above range, the comprehensive effect of the obtained product is more excellent.
[0018] As a preferred embodiment of the self-adhesive layer composition of the present invention, the grafting rate of the maleic anhydride grafted polypropylene is 0.4-1.5%.
[0019] The grafting rate of maleic anhydride grafted polypropylene was tested by referring to the grafting rate of MAH according to the acid-base titration method.
[0020] Exemplarily, the grafting rate of the maleic anhydride grafted polypropylene can be any point value or any two point range values between 0.4-1.5%, such as 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, etc.
[0021] Preferably, the grafting rate of the maleic anhydride grafted polypropylene is 0.8-1.2%.
[0022] The present invention has found that the grafting rate of maleic anhydride grafted polypropylene can increase the compatibility of the weathering additive and the base resin within a certain range, thereby improving the weather resistance of the product and ensuring the high light transmittance of the product.
[0023] As a preferred embodiment of the self-adhesive layer composition of the present invention, in the light absorber, the mass ratio of 2-hydroxy-4-n-octyloxybenzophenone (UV-531) and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol (UV-326) is (0-1.5):1.
[0024] Preferably, in the light absorber, the mass ratio of 2-hydroxy-4-n-octyloxybenzophenone (UV-531) to 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol (UV-326) is (0.1-1.5):1.
[0025] Exemplarily, the mass ratio of the 2-hydroxy-4-n-octyloxybenzophenone and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol may be any point value or any two point range values between (0.1-1.5):1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, etc.
[0026] As a preferred embodiment of the self-adhesive layer composition of the present invention, in the light stabilizer, the mass ratio of the polymeric hindered amine light stabilizer to 1,5,8,12-tetrakis[4,6-bis(N-butyl-N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane (UV-119) is (0-8):1.
[0027] Preferably, the mass ratio of the polymeric hindered amine light stabilizer to 1,5,8,12-tetrakis[4,6-bis(N-butyl-N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane is (0.5-8):1.
[0028] Exemplarily, the mass ratio of the polymeric hindered amine light stabilizer to 1,5,8,12-tetrakis[4,6-bis(N-butyl-N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane can be any point value or any two point range values between (0.5-8):1, for example, it can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, etc.
[0029] Preferably, the polymeric hindered amine light stabilizer includes UV-944.
[0030] As a preferred embodiment of the self-adhesive layer composition of the present invention, the number average molecular weight of the styrene-based thermoplastic elastomer is 30,000-90,000, and the styrene content is 8-33%.
[0031] The test method for the styrene content in styrene-based thermoplastic elastomers is to refer to the Fourier transform attenuated total reflectance infrared spectroscopy (FTIR-ATR) method to determine the total styrene content at different concentrations, and the number average molecular weight is characterized by gel permeation chromatography (GPC).
[0032] Exemplarily, the number average molecular weight of the styrene-based thermoplastic elastomer can be any point value between 30,000 and 90,000 or a value between any two points, for example, it can be 50,000-60,000, 50,000-90,000, etc., or it can be 30,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000, etc. Within the range of 30,000-90,000 given in the present invention, the technical effects of the present invention can be achieved; in the styrene-based thermoplastic elastomer, the styrene content can be any point value between 8-33% or a range of values between any two points, for example, the styrene content can be 13-15%, 8-15%, 15-33%, etc., or it can be 8%, 10%, 12%, 14%, 16%, 18%, 20%, 22%, 25%, 28%, 30%, 33%, etc. Within the range of 8-33% given in the present invention, the technical effects of the present invention can be achieved.
[0033] Preferably, the number average molecular weight of the styrene-based thermoplastic elastomer is 50,000-60,000, and the styrene content is 12-15%.
[0034] As a preferred embodiment of the self-adhesive layer composition of the present invention, the styrene-based thermoplastic elastomer includes at least one of SBS, SEBS, SIS and SEPS.
[0035] As a preferred embodiment of the self-adhesive layer composition of the present invention, the number average molecular weight of the tackifying resin is 400-2000 g / mol.
[0036] The testing method for the number average molecular weight of the tackifying resin is carried out with reference to GB / T21863-2008.
[0037] Exemplarily, the number average molecular weight of the tackifying resin can be any point value or any two point range values between 400-2000 g / mol, such as 500-1000 g / mol, 500-1200 g / mol, 1200-2000 g / mol, etc., or can be 400 g / mol, 600 g / mol, 800 g / mol, 1000 g / mol, 1200 g / mol, 1400 g / mol, 1600 g / mol, 1800 g / mol, 2000 g / mol, etc.
[0038] Preferably, the number average molecular weight of the tackifying resin is 1000-1200 g / mol.
[0039] As a preferred embodiment of the self-adhesive layer composition of the present invention, the tackifying resin is at least one of hydrogenated petroleum resin, terpene resin and rosin ester.
[0040] In the second aspect of the present invention, the present invention provides a high-transmittance and super-weather-resistant protective film, which comprises a self-adhesive layer, a core layer and a surface layer from bottom to top, wherein the self-adhesive layer comprises the self-adhesive layer composition of the present invention.
[0041] As a preferred embodiment of the high-transmittance and super-weather-resistant protective film of the present invention, the thickness of the self-adhesive layer is 5-15 μm, and the thickness ratio of the self-adhesive layer, the core layer and the surface layer is 1:(2-12):1.
[0042] Preferably, the thickness ratio of the adhesive layer, the core layer and the surface layer is 1:(3-5):1.
[0043] The inventors have found that when the thickness ratio of the self-adhesive layer, the core layer and the surface layer is within the above range, the performance of the obtained product is better.
[0044] As a preferred embodiment of the high-transmittance and super-weather-resistant protective film of the present invention, the core layer comprises the following components in parts by weight: 99-100 parts of base resin A and 0-1 part of auxiliary agent A.
[0045] As a preferred embodiment of the high-transmittance and super-weather-resistant protective film of the present invention, the surface layer comprises the following components in parts by weight: 99-100 parts of base resin B and 0-1 part of auxiliary agent B.
[0046] Preferably, the base resin A and the base resin B are each independently selected from polypropylene or polyethylene, and the auxiliary agent A and the auxiliary agent B are each independently selected from at least one of an antioxidant, a weathering agent, an anti-blocking agent, and a lubricant.
[0047] More preferably, the melt index of the polypropylene or polyethylene is 3-15 g / 10 min. The melt index of the polypropylene is tested at 230° C. and 2.16 kg, and the melt index of the polyethylene is tested at 190° C. and 2.16 kg.
[0048] The effects of the present invention can be achieved within the range of the melt index of the polypropylene or polyethylene given in the present invention; illustratively, the melt index of the polypropylene or polyethylene may be 3 g / 10min, 5 g / 10min, 7 g / 10min, 9 g / 10min, 11 g / 10min, 12 g / 10min, or 15 g / 10min.
[0049] In a third aspect of the present invention, the present invention provides a method for preparing the high-transmittance and super-weather-resistant protective film, the preparation method comprising the following steps:
[0050] (1) respectively mixing the components of the self-adhesive layer, the core layer and the surface layer to obtain a self-adhesive layer premix, a core layer premix and a surface layer premix;
[0051] (2) extruding and granulating the self-adhesive layer premix to obtain a self-adhesive layer material;
[0052] (3) The self-adhesive layer material, the core layer premix and the surface layer premix are co-blown into a film to obtain the high-transmittance and ultra-weather-resistant protective film.
[0053] The preparation method of the high-transmittance and super-weather-resistant protective film of the present invention is simple, and products with different layer thicknesses and different overall thicknesses can be produced according to actual use needs, and the industrial-scale production efficiency is high.
[0054] As a preferred embodiment of the preparation method of the present invention, in the step (3), the core layer premix, the surface layer premix and the self-adhesive layer material are respectively put into the core layer barrel, the surface layer barrel and the self-adhesive layer barrel of the film blowing machine to form a film through co-blowing.
[0055] As a preferred embodiment of the preparation method of the present invention, in the step (2), the temperature of the extrusion granulation is 160-190°C.
[0056] In the fourth aspect of the present invention, the present invention provides the use of the high-transmittance and super-weather-resistant protective film in the preparation of electrical protective films.
[0057] Exemplarily, the high-transmittance and ultra-weather-resistant protective film is used in the preparation of elevator protective film.
[0058] Beneficial effects of the present invention:
[0059] The present invention provides a high-transmittance and super-weather-resistant protective film having a basic peeling force, and also having good light transmittance and weather resistance. Specifically, the peeling force of the obtained high-transmittance and super-weather-resistant protective film is between 2.9-4.2N / 25mm, the light transmittance is above 89.2%, and the white glue area is 2.7mm after irradiation under ultraviolet light for 1000h. 2 / m 2 The number of white spots precipitated after 15 days of testing at a temperature of 85°C and a humidity of 85% is 9 / m 2 the following. DETAILED DESCRIPTION
[0060] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments and comparative examples, the purpose of which is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The experimental reagents and instruments designed for the implementation of the present invention and the comparative examples, unless otherwise specified, are all commonly used ordinary reagents and instruments; and the raw materials used in the parallel experiments of the embodiments of the present invention and the comparative examples are consistent.
[0061] The raw materials used in the embodiments, comparative examples and effect examples of the present invention are as follows:
[0062] SBCs1: SEBS, SEBS G1645, number average molecular weight 50,000, styrene content 13%, Kraton, USA;
[0063] SBCs2: SIS, SIS 4113N, number average molecular weight 50,000, styrene content 15%, Taiwan Synthetic Rubber Co., Ltd., China;
[0064] SBCs3: SEBS, SEBS G1651, number average molecular weight 90,000, styrene content 33%, Kraton, USA;
[0065] Maleic anhydride grafted polypropylene 1: WP128, grafting rate 0.8%, Ningbo Nengzhiguang;
[0066] Maleic anhydride grafted polypropylene 2: Fine-Blend FB122, grafting rate 1.2%, Shanghai Jiayirong;
[0067] Maleic anhydride grafted polypropylene 3: YBL-1172, grafting rate 0.4%, Kingfa Science & Technology Co., Ltd.;
[0068] Maleic anhydride grafted polypropylene 4: PC-1-1, grafting rate 1.5%, Nanhai Bochen Polymer Materials Co., Ltd.;
[0069] Maleic anhydride grafted POE: PC-8C, grafting rate 0.8%, Nanhai Bochen Polymer Materials Co., Ltd.;
[0070] Tackifying resin 1: hydrogenated petroleum resin, HH140, molecular weight 1200 g / mol, Guangdong Xinhua Yue Resin Technology Co., Ltd.;
[0071] Tackifying resin 2: terpene resin, SYLVARES TR7125, molecular weight 1030 g / mol, Kraton, USA;
[0072] Tackifying resin 3: hydrogenated petroleum resin, Impera P1504, molecular weight 560 g / mol, Eastman, USA;
[0073] Polyethylene 1: melt index is 3.5g / 10mol, model is LLDPE 3518CA, manufacturer is ExxonMobil of the United States;
[0074] Polyethylene 2: melt index is 15g / 10mol, model is LLDPE 5815, manufacturer is Dow Chemical of the United States;
[0075] Light absorber 1: 2-hydroxy-4-n-octyloxybenzophenone, UV-531, commercially available;
[0076] Light absorber 2: 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol, UV-326, Tianjin Lianlong New Materials Co., Ltd.;
[0077] Light absorber 3: 2,2'-methylenebis[6-(2H-benzodiyl)-4-(1,1,3,3-tetramethylbutyl)phenol, UV-360, commercially available;
[0078] Light stabilizer 1: polymeric hindered amine light stabilizer, UV-944, CAS 71878-19-8, molecular formula (C 35 H 66 N8) n , average molecular weight is 2100-3000, Nanjing Milan Chemical Co., Ltd.;
[0079] Light stabilizer 2: 1,5,8,12-tetrakis[4,6-bis(N-butyl-N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane, UV-119, average molecular weight 2286, Tianjin Lianlong New Materials Co., Ltd.;
[0080] Light stabilizer 3: UV-770, CAS number is 52829-07-9, molecular formula is C 28 H 52 O4N2, average molecular weight 481, Tianjin Lianlong New Materials Co., Ltd.;
[0081] Light stabilizer 4: UV-622, CAS number is 65447-77-0, molecular formula is H[C 15 H 25 O4N] n OCH3, average molecular weight 3100-4000, Hubei Hengluyuan Technology Co., Ltd.;
[0082] Antioxidant: a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, commercially available;
[0083] Weathering agent: 2-hydroxy-4-n-octyloxybenzophenone, UV-531, commercially available;
[0084] Opening agent: diatomaceous earth, commercially available;
[0085] Lubricant: erucamide, commercially available.
[0086] Examples 1-18 and Comparative Examples 1-8
[0087] The embodiments and comparative examples of the present invention provide a high-transmittance and ultra-weather-resistant protective film, wherein the core layer comprises the following components in parts by mass: 89.8 parts of polyethylene 1, 10 parts of polyethylene 2, 0.1 parts of an antioxidant, and 0.1 parts of a weathering agent;
[0088] The surface layer includes the following components in parts by mass: 100 parts of polyethylene 1, 0.1 parts of antioxidant, 0.1 parts of weathering agent, 0.5 parts of anti-blocking agent, and 0.3 parts of lubricating agent;
[0089] The self-adhesive layer includes the components shown in Table 1-3 (parts by weight):
[0090] Table 1
[0091]
[0092] Table 2
[0093]
[0094]
[0095] Table 3
[0096]
[0097]
[0098] The preparation methods of the embodiments of the present invention and the comparative examples are as follows:
[0099] (1) respectively mixing the components of the self-adhesive layer, the core layer and the surface layer to obtain a self-adhesive layer premix, a core layer premix and a surface layer premix;
[0100] (2) extruding and granulating the self-adhesive layer premix to obtain a self-adhesive layer material;
[0101] (3) putting the core layer premix, the surface layer premix and the self-adhesive layer material into the core layer material barrel, the surface layer material barrel and the self-adhesive layer material barrel of the film blowing machine respectively, and forming a film by co-blowing to obtain a high-transmittance and super-weather-resistant protective film;
[0102] The thickness of the self-adhesive layer in Examples 1-18 and Comparative Examples 1-8 is 10 μm, and the thickness ratio of the self-adhesive layer, the core layer and the surface layer is 1:5:1.
[0103] Embodiment 19
[0104] The present embodiment provides a high-transmittance and ultra-weather-resistant protective film. The only difference between the high-transmittance and ultra-weather-resistant protective film and Embodiment 1 is that the core layer comprises the following components in parts by mass: 80 parts of polyethylene 1, 19 parts of polyethylene 2, 0.1 parts of antioxidant and 0.1 parts of weather-resistant agent; the surface layer comprises the following components in parts by mass: 99 parts of polyethylene 1, 0.1 parts of antioxidant, 0.1 parts of weather-resistant agent, 0.5 parts of opening agent and 0.3 parts of lubricant.
[0105] Embodiment 20
[0106] This embodiment provides a high-transmittance and super-weather-resistant protective film. The only difference between the high-transmittance and super-weather-resistant protective film and Embodiment 1 is that the thickness of the self-adhesive layer is 14 μm, and the thickness ratio of the self-adhesive layer, the core layer and the surface layer is 1:3:1.
[0107] Embodiment 21
[0108] This embodiment provides a high-transmittance and super-weather-resistant protective film. The only difference between the high-transmittance and super-weather-resistant protective film and Embodiment 1 is that the thickness of the self-adhesive layer is 17.5 μm, and the thickness ratio of the self-adhesive layer, the core layer and the surface layer is 1:2:1.
[0109] Embodiment 22
[0110] This embodiment provides a high-transmittance and super-weather-resistant protective film. The only difference between the high-transmittance and super-weather-resistant protective film and embodiment 1 is that the thickness of the self-adhesive layer is 5 μm, and the thickness ratio of the self-adhesive layer, core layer and surface layer is 1:12:1.
[0111] Effect example
[0112] The effect examples of the present invention verify the performance of the high-transmittance and super-weather-resistant protective films prepared in Examples 1-22 and Comparative Examples 1-8, including the following aspects:
[0113] 1. Peel force: Tested in accordance with GB / T2792-2014;
[0114] 2. Light transmittance: Tested in accordance with GB / T 2410-2008;
[0115] 3. Weather resistance: Refer to the method in GB / T2792-2014 to select steel plates and pre-treat them, and paste the prepared protective film on the steel plates by rolling. After UVB-313 (type 2), 0.48W / (m 2·nm) After 1000h of ultraviolet irradiation, use a tensile testing machine to continuously peel at a rate of 5mm / s according to the method in GB / T2792-2014. After the peeling is completed, observe whether there is residual glue on the surface of the iron plate. If there is residual glue, record the area of residual glue;
[0116] 4. Precipitation test: Place the prepared protective film in an aging box at a temperature of 85°C and a humidity of 85% for precipitation test. The test time is 15 days. Observe whether there are white spots on the surface of the protective film. If there are white spots, record the number of white spots.
[0117] The results are shown in Table 4 (the industry requires that the weather-resistant residual adhesive area is less than 3mm 2 / m 2 The number of white spots is less than 10 / m 2 );
[0118] Table 4
[0119]
[0120]
[0121] It can be seen from Table 4 that the product obtained by adopting the technical solution of the present invention has a suitable range of peeling force, which is between 2.9-4.2N / 25mm; at the same time, the obtained product has good light transmittance and weather resistance, with a light transmittance of more than 89.2%, and the residual adhesive area after 1000h of ultraviolet irradiation is 2.7mm 2 / m 2 Below, the number of white spots after double 85 test is 9 / m 2 the following;
[0122] It can be seen from Example 1, Examples 6-11 and Comparative Examples 1-2 that the mass ratio of the light absorber to the light stabilizer in the weathering aid will affect the performance of the product. When the mass ratio of the light absorber to the light stabilizer in Comparative Examples 1-2 is not within the given range, the weathering performance of the obtained product material cannot meet the requirements, and the light transmittance of the material also decreases to a certain extent.
[0123] It can be seen from Example 1 and Comparative Examples 3-4 that light absorbers and light stabilizers are indispensable. When no light stabilizer is added in Comparative Example 3, the residual adhesive area of the obtained product is greater than 3 mm. 2 / m 2 The performance of the product cannot meet the requirements, and the high temperature and high humidity resistance is also poor; when no light absorber is added in Comparative Example 4, the residual glue area of the obtained product is greater than 3mm 2 / m 2 , and the product's resistance to high temperature and humidity cannot meet the requirements;
[0124] It can be seen from Example 1 and Comparative Examples 5-7 that the selection of light absorber and light stabilizer will also affect the performance of the product. When the light absorber or light stabilizer in Comparative Examples 5-7 is not within the range given in the present invention, the weather resistance of the obtained product material cannot meet the requirements, and the residual adhesive area is greater than 3mm 2 / m 2 At the same time, the light transmittance of the material also decreases to a certain extent, and the precipitation of the material increases;
[0125] It can be seen from Example 1, Examples 16-18 and Comparative Example 8 that maleic anhydride grafted polypropylene will also affect the performance of the product. When maleic anhydride grafted polypropylene is not used in Comparative Example 8, the precipitation of the obtained product material is significantly increased, far exceeding the product performance requirements, and the light transmittance of the product is also significantly reduced.
[0126] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A self-adhesive layer composition, characterized in that: The self-adhesive layer composition comprises the following components in parts by weight: 53-82 parts of styrene-based thermoplastic elastomer, 13-37 parts of tackifying resin, 2-9 parts of maleic anhydride grafted polypropylene, and 0.1-1 parts of weathering agent; The weathering agent comprises a light absorber and a light stabilizer, wherein the mass ratio of the light absorber to the light stabilizer is light absorber:light stabilizer=(1-1.5):1; The light absorber includes at least one of 2-hydroxy-4-n-octyloxybenzophenone and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol; The light stabilizer includes at least one of a polymeric hindered amine light stabilizer and 1,5,8,12-tetrakis[4,6-bis(N-butyl-N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane, and the average molecular weight of the light stabilizer is 2000-3000.
2. The self-adhesive layer composition according to claim 1, characterized in that: The self-adhesive layer composition comprises the following components in parts by weight: 5-6 parts of maleic anhydride grafted polypropylene and 0.4-0.6 parts of a weathering aid.
3. The self-adhesive layer composition according to claim 1, characterized in that The grafting rate of the maleic anhydride grafted polypropylene is 0.4-1.5%.
4. The self-adhesive layer composition according to claim 1, characterized in that Satisfy at least one of the following: a. In the light absorber, the mass ratio of 2-hydroxy-4-n-octyloxybenzophenone and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol is (0-1.5):1; preferably, the mass ratio of 2-hydroxy-4-n-octyloxybenzophenone and 2-(5-chloro-2-benzotriazolyl)-6-tert-butyl-p-cresol is (0.1-1.5):1; b. In the light stabilizer, the mass ratio of the polymeric hindered amine light stabilizer to 1,5,8,12-tetrakis[4,6-bis(N-butyl-N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane is (0-8):1; preferably, the mass ratio of the polymeric hindered amine light stabilizer to 1,5,8,12-tetrakis[4,6-bis(N-butyl-N-1,2,2,6,6-pentamethyl-4-piperidinylamino)-1,3,5-triazine-2-yl]-1,5,8,12-tetraazadodecane is (0.5-8):
1.
5. The self-adhesive layer composition according to claim 1, characterized in that: Satisfy at least one of the following: c. The styrene-based thermoplastic elastomer has a number average molecular weight of 30,000-90,000 and a styrene content of 8-33%; d. The styrene-based thermoplastic elastomer includes at least one of SBS, SEBS, SIS, and SEPS; e. The number average molecular weight of the tackifying resin is 400-2000g / mol; f. The tackifying resin is at least one of hydrogenated petroleum resin, terpene resin and rosin ester.
6. A high-transmittance and super-weather-resistant protective film, characterized in that: The invention comprises a self-adhesive layer, a core layer and a surface layer in order from bottom to top, wherein the self-adhesive layer comprises the self-adhesive layer composition according to any one of claims 1 to 5.
7. The high-transmittance and super-weather-resistant protective film according to claim 6, characterized in that: The thickness of the self-adhesive layer is 5-15 μm, and the thickness ratio of the self-adhesive layer, the core layer and the surface layer is 1:(2-12):
1.
8. The high-transmittance and super-weather-resistant protective film according to claim 6, characterized in that: The core layer comprises the following components in parts by weight: 99-100 parts of base resin A and 0-1 part of auxiliary agent A; And / or, the surface layer comprises the following components in parts by weight: 99-100 parts of base resin B and 0-1 part of auxiliary agent B.
9. The method for preparing a high-transmittance and super-weather-resistant protective film according to any one of claims 6 to 8, characterized in that: The following steps are involved: (1) respectively mixing the components of the self-adhesive layer, the core layer and the surface layer to obtain a self-adhesive layer premix, a core layer premix and a surface layer premix; (2) extruding and granulating the self-adhesive layer premix to obtain a self-adhesive layer material; (3) The self-adhesive layer material, the core layer premix and the surface layer premix are co-blown into a film to obtain the high-transmittance and super-weather-resistant protective film.
10. Use of the high-transmittance and ultra-weather-resistant protective film according to any one of claims 6 to 8 in the preparation of electrical protective films.
Citation Information
Patent Citations
Super-weather-resistant solar cell protecting film and preparation method thereof
CN109367146A
Composite light stabilizer suitable for rigid polyvinyl chloride material, rigid polyvinyl chloride material and preparation method of rigid polyvinyl chloride material
CN114316471A
Modified polypropylene material as well as preparation method and application thereof
CN116836505A
Protective film easy to unwind and high in stripping force as well as preparation method and application of protective film
CN117467383A
High clarity and low haze UV stabilized styrene and methyl methacrylate copolymers
US20240317968A1